EFFECT OF JOB SATISFACTION SATISFACTION ON TURNOVER INTENTION: CASE STUDY ON ADIRA QUANTUM MATARAM - I Gede Bayu Wijaya (Journal of Research in Business, Economics, and Education, 2020)
Employees who are satisfied with their work will appear in employees' emotions. Employee satisfaction will make employees love their work. Job satisfaction is enjoyed at work, outside of work, and a combination of inside and outside work, thus employees who are satisfied with their work, and enjoy their work will survive in the company despite many offers from other companies that promise better welfare. Vice versa, an employee who is less satisfied with his work, will feel uncomfortable working, does not show good performance and achievement is lacking and various problems occur. This study aims to determine the effect of job satisfaction on employee desires at PT. Adira Quantum Mataram Branch. The population in the study were all employees with a total of 155 people, and obtained a sample of 21 people. The results of multiple linear regression analysis show that job satisfaction factors consisting of fairness of compensation, salary satisfaction and organizational climate show a simultaneous flow towards the desires of employees. The job satisfaction variable contained in the justice compensation variable, salary satisfaction, organizational climate has a significant negative effect on employee desires (Y), this can be seen in the regression coefficient has the highest significant level value that is t> 0.046, meaning that if more high dissatisfaction of employees will increase the desire to leave employees, so also if the higher the sense of satisfaction felt by employees will reduce the level of desire to leave employees to find another job), where in this research the calculation results obtained for job satisfaction amounted to 0.783.